1978
DOI: 10.1007/bf00273770
|View full text |Cite
|
Sign up to set email alerts
|

Effect of test environment on expression of clines and on delimitation of seed zones in Douglas-fir

Abstract: Clinal models of population structure in an indigenous tree species can be used to delineate seedcollection zones and breeding zones, and to devise transfer rules. Models may be developed by growing populations in test environments; however, a clinal description may be a function of test environments as well as of population genotypes. This possibility was studied by growing seedlings from 40 populations of northwestern U.S. Douglas-fir (Pseudotsuga menziesii var. 'menziesii' [Mirb.] Franco) in eight nursery-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 13 publications
3
57
0
Order By: Relevance
“…High-elevation provenances grew poorly at low-elevation sites in general. Such macro-geographic variation pattern generally follows the results revealed by juvenile traits (e.g., CAMPBELL and SORENSEN, 1978;GRIFFIN, 1978;ST CLAIR et al, 2005). Based on the empirical equations in Table 6, moving a provenance away from its original sites 500 m in elevation or 800 km in latitude would cause on average 9 % loss in total volume per plot at rotation.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…High-elevation provenances grew poorly at low-elevation sites in general. Such macro-geographic variation pattern generally follows the results revealed by juvenile traits (e.g., CAMPBELL and SORENSEN, 1978;GRIFFIN, 1978;ST CLAIR et al, 2005). Based on the empirical equations in Table 6, moving a provenance away from its original sites 500 m in elevation or 800 km in latitude would cause on average 9 % loss in total volume per plot at rotation.…”
Section: Discussionsupporting
confidence: 75%
“…The potential problems with "local is best" recommendations are: (1) there is a risk of encouraging the establishment of populations that do not harbor sufficient genetic variation and evolutionary potential, and therefore reduce the potential genetic gains though long-term breeding; and (2) it increases the cost of tree improvement beyond the level necessary. While results from several nursery or short-term provenance or genecology studies led to conclusions of local adaptation in coastal Douglas-fir (e.g., CAMPBELL and SORENSEN, 1978;GRIFFIN, 1978;SILEN and MANDEL, 1983;ST CLAIR et al, 2005), early reports on the longterm provenance studies suggested that maladaptation was not a big problem unless seed transfer involved large altitudinal distances. Several tree breeders (WOODS, 1993;STONECYPHER et al, 1996) advocated using far larger breeding zones in this region than the original IFA-progressive plan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Campbell and Sorensen (1978), the need for seed zones in artificial afforestation was recognized long ago. In seed zoning, forest lands are stratified into units within which interactions between genotype and environment approach zero.…”
Section: Introduction Ecological Adaptations Within Northern Rocky Momentioning
confidence: 99%
“…level of phenotypic variation that is strongly associated with geographic, topographic, and climatic features (Campbell and Sugano 1975;Campbell and Sorensen 1978;Steiner 1979;Li and Adams 1993;Aitken and Adams 1997;Anekonda et al 2000;St. Clair et al 2005;St.…”
mentioning
confidence: 99%